Helicobacter pylori promotes intestinal flora imbalance and hepatic metabolic disorders under arsenic stress - Linmin Zhong; Qiling Yang; Yiming Shao; Shanwen Hu; Lianxian Guo (Ecotoxicology and Environmental Safety)
Environmental arsenic contamination is a serious issue that cannot be ignored, since arsenic levels in drinking water frequently exceed safety standards, and there is an increased prevalence of Helicobacter pylori (H. pylori) infection. This results in an increasing population at risk of simultaneous exposure to both harmful agents, yet whether a synergistic interaction exists between them remains unclear. Therefore, this study aims to investigate the combined effects and underlying pathogenic mechanisms of concurrent exposure to these two hazardous factors by establishing a mouse model that is infected with H. pylori and exposed to inorganic arsenic through drinking water. Analysis of intestinal flora revealed significant alterations in the composition, relative abundance (Akkermansia, Faecalibaculum, Ilieibacterium, etc.), and metabolic potential of the intestinal microflora (amino acid metabolism and energy metabolism) in the combinatory exposure group. Non-targeted metabolomics analysis identified that the combinatory exposure group exhibited greater fluctuations in metabolite content, particularly in triacylglycerol, fatty-acid, peptide and amino acid. Moreover, H. pylori infection and arsenic exposure had increased levels of metabolites associated with the intestinal microbiota in their livers (4-Ethylphenyl sulfate and Phenylacetylglycine). Further analysis revealed significant correlations between changes in the intestinal flora and alterations in liver metabolic profiles. Herein, we hypothesize that H. pylori infection may exacerbate the intestinal flora imbalance and hepatic metabolic disturbances caused by arsenic exposure, which may disrupt enterohepatic homeostasis and potentially increase biological susceptibility to heavy metal toxicity.